ANALISIS UPAYA PENYELUNDUPAN HUKUM DALAM UPAYA MENGHINDARI SYARAT JANGKA WAKTU 90 HARI DALAM MENGAJUKAN GUGATAN KE PERADILAN TATA USAHA NEGARA (STUDI PUTUSAN NOMOR 51/G/2020/PTUN.PLG) - Adimas Gusti Darmansya; Rasji Rasji (Fakultas Hukum Universitas Tarumanagara, 2021)
The objective of the Unitary State of the Republic of Indonesia as stated in paragraph four of the Preamble to the 1945 Constitution is to promote public welfare and participate in implementing world order based on independence. With the aim of general welfare, should there be something that harms one of the parties, the aggrieved party can file a lawsuit to the competent court, so that no more party is harmed and a sense of justice can be felt by all parties, thus the purpose of the general welfare can be achieved and run well.